Internet of Things (Iot)-Based Air Conditioner Control And Monitoring System at Al Firdaus Preschool Education Park (TPP) Surakarta - Susanto, Rudi; Muhammad, Nibras Faiq; Sutarji, S (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
The use of conventional air conditioners is often inefficient and energy-wasteful. Users usually set the temperature manually, which can result in excessive energy use. In addition, the lack of an effective monitoring system makes it difficult to monitor air conditioning conditions, such as room temperature and humidity. This research aims to create an Air Conditioner monitoring and control device that can work automatically to control the temperature in a room and can be controlled through IOT. A temperature monitoring system and remote air conditioning controller is a tool that can be used to monitor room temperature conditions and control the temperature in the room to match what we want. This tool uses proportional type control (P) with a monitoring system utilizing Internet of Things (IoT) technology. The ESP 32 microcontroller is used as a microcontroller-based control device that has been facilitated with a wifi module. To measure the room temperature, a DHT11 sensor and an infrared LED are assembled and connected to a microcontroller as a data transmitter to the air conditioning unit. This system uses the arduino IDE application which has features to monitor and control the temperature in the room. The way this tool works is as a remote that controls the Air Conditioner to get the desired temperature in the room and the temperature read on the device can be monitored on a smartphone remotely.